A constitutive framework for the elastoplastic modelling of geomaterials. (15th June 2015) - Mortara, Giuseppe
Abstract: The object of this paper is the definition of a generalised constitutive model for geomaterials, based on elastoplasticity. Two are the tasks of the paper: the substantial enhancement of an existing hierarchical yield function and the definition of an isotropic hardening constitutive model for the behaviour of both cohesive and frictional geomaterials. After its definition, the new function will be compared with different yield surfaces existing in literature in both the deviatoric and the meridian representation. Thereafter, the constitutive model will be outlined by defining hierarchical expressions for hardening laws and stress–dilatancy relationship in order to take into account several aspects of soil behaviour. Finally, some comparisons between data from experimental tests on clay and sand will be made to highlight the hierarchical structure of the proposed model.